Cancer screening in the United States, 2018: A review of current American Cancer Society guidelines and current issues in cancer screening - Smith, Robert A.; Andrews, Kimberly S.; Brooks, Durado; Fedewa, Stacey A.; Manassaram‐Baptiste, Deana; Saslow, Debbie; Brawley, Otis W.; Wender, Richard C. (CA: a cancer journal for clinicians, 2018)
Each year, the American Cancer Society publishes a summary of its guidelines for early cancer detection, data and trends in cancer screening rates from the National Health Interview Survey, and select issues related to cancer screening. In this 2018 update, we also summarize the new American Cancer Society colorectal cancer screening guideline and include a clarification in the language of the 2013 lung cancer screening guideline. CA Cancer J Clin 2018;68:297–316. © 2018 American Cancer Society.